Mechanism for Detecting Black Hole Attack in Infrastructure-Less MANET (MDB-MAN) - Ahmed, Syed Muqtar; Sattar, Syed Abdul (International Journal of Computer Sciences and Engineering, 2018)
Mobile Adhoc Network (MANET) is a self-organized group of wireless nodes forming a tentative network. In MANET nodes would be randomly changing their positions due to its dynamic infrastructure-less property. Therefore it is more susceptible to Black-Hole & Gray-Hole attacks, which are considered as serious attacks to the network. So far several solutions have been developed for MANET but many of them are not efficient. The main purpose of this paper is to present a solution known as mechanism for detecting Black Hole Attack in Infrastructure-Less MANET (MDB-MAN). An Algorithm is developed to detect Black-Hole node based on reactive Adhoc on demand distance vector protocol (AODV), where routes are established on demand. Several times simulations were conducted on proposed model using Network Simulator and found that the Packet Delivery Ratio (PDR) and Throughput is almost similar at time instant 50 msec. as compared to original AODV protocol. The Packet Drop Ratio keeps on changing as time changes and it can be tolerable.